Group II introns: versatile ribozymes and retroelements. (15th February 2016) - McNeil, Bonnie A.; Semper, Cameron; Zimmerly, Steven
Abstract : Group II introns are catalytic RNAs (ribozymes) and retroelements found in the genomes of bacteria, archaebacteria, and organelles of some eukaryotes. The prototypical retroelement form consists of a structurally conserved RNA and a multidomain reverse transcriptase protein, which interact with each other to mediate splicing and mobility reactions. A wealth of biochemical, cross‐linking, and X‐ray crystal structure studies have helped to reveal how the two components cooperate to carry out the splicing and mobility reactions. In addition to the standard retroelement form, group II introns have evolved into derivative forms by either losing specific splicing or mobility characteristics, or becoming functionally specialized. Of particular interest are the eukaryotic derivatives—the spliceosome, spliceosomal introns, and non‐LTR retroelements—which together make up approximately half of the human genome. On a practical level, the properties of group II introns have been exploited to develop group II intron‐based biotechnological tools. WIREs RNA 2016, 7:341–355. doi: 10.1002/wrna.1339 This article is categorized under: RNA Processing > Splicing Mechanisms RNA-Based Catalysis > RNA Catalysis in Splicing and Translation